The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s12034-008-0108-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of radio frequency power on structure and ionic conductivity of LiPON thin films

Abstract: Lithium phosphorus oxynitride (LiPON) thin films as solid electrolytes were prepared by radio frequency magnetron sputtering of a Li 3 PO 4 target in ambient nitrogen atmosphere. The influence of radio frequency (rf) power on the structure and the ionic conductivity of LiPON thin films has been investigated. The morphology, composition, structure and ionic conductivity of thin films were characterized by scanning electron microscopy, energy dispersive spectroscopy, X-ray diffraction, X-ray photoelectron spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 25 publications
5
34
0
Order By: Relevance
“…These changes make it easier for the lithium ion to break its bond with oxygen and easier movement through channels. Also, a study of amorphous phosphorous nitrides by Veprek et al on nitrogen incorporation as doubly (−N =) and more distorted triply coordinated (−N b) states to phosphate glasses revealed greater ionic conductivity with increased presence of (−N b) states [1,21,22].…”
Section: Resultsmentioning
confidence: 99%
“…These changes make it easier for the lithium ion to break its bond with oxygen and easier movement through channels. Also, a study of amorphous phosphorous nitrides by Veprek et al on nitrogen incorporation as doubly (−N =) and more distorted triply coordinated (−N b) states to phosphate glasses revealed greater ionic conductivity with increased presence of (−N b) states [1,21,22].…”
Section: Resultsmentioning
confidence: 99%
“…As ionic conductivity increases with nitrogen content, either the number of mobile lithium ions also increases and/or the mobility of lithium ions is improved as a consequence of some structural and/or electronic modifications in the material. In numerous studies [4,7,21], the lithium content remains nearly constant with nitridation, and the authors, supposing that all lithium ions are mobile, have explained the conductivity increase by a change of bonding structure. Nevertheless, the NMR 7 Li studies led for the first time on LiPON thin films have clearly evidenced that only a part of lithium ions are mobile and participate in the conduction process.…”
Section: Discussionmentioning
confidence: 99%
“…It has been claimed that the higher the N t /N d ratio, the higher will be the ionic conductivity of LiPON thin 0378-7753/$ -see front matter © 2010 Elsevier B.V. All rights reserved. doi:10.1016/j.jpowsour.2010.12.022 films [22]. The ratio of these signals was found to be dependent on the power density during deposition, but the results are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of these signals was found to be dependent on the power density during deposition, but the results are controversial. On one side Roh et al [19] and Hamon et al [15] observed an increase of the conductivity by decreasing the power density, on the other side Hu et al [22] and Choi et al [18] reported the opposite behaviour. Additionally, Iriyama et al [24] investigated an influence of an annealing temperature of 473 K in air on the interface between LiCoO 2 and LiPON and found a decreased charge transfer resistance at the interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation